2023
DOI: 10.1111/jsr.14028
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering sleep perception in insomnia: from misperception to mismeasurement

Aurélie M. Stephan,
Francesca Siclari

Abstract: SummarySo‐called ‘sleep misperception’ refers to a phenomenon in which individuals have the impression of sleeping little or not at all despite normal objective measures of sleep. It is unknown whether this subjective–objective mismatch truly reflects an abnormal perception of sleep, or whether it results from the inability of standard sleep recording techniques to capture ‘wake‐like’ brain activity patterns that could account for feeling awake during sleep. Here, we systematically reviewed studies reporting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 93 publications
0
1
0
Order By: Relevance
“…This finding is consistent with the evidence in the literature reporting that the NREM sleep of ID patients is characterized by more cortical activation than in healthy con-trols. Several studies have reported an increase in alpha [13,[44][45][46], sigma [13,44,45], beta [13,17,[44][45][46], gamma [17,46,47] frequencies and a decrease in delta frequencies [17,[44][45][46] during an entire night's NREM sleep [48]. It was also found that ID patients exhibited increased beta frequencies even during diurnal sleep, as observed in multiple sleep latency tests (MSLTs), and those with lower sleep efficiency and longer latency to MLST showed higher beta power also during night sleep [49].…”
Section: Discussionmentioning
confidence: 96%
“…This finding is consistent with the evidence in the literature reporting that the NREM sleep of ID patients is characterized by more cortical activation than in healthy con-trols. Several studies have reported an increase in alpha [13,[44][45][46], sigma [13,44,45], beta [13,17,[44][45][46], gamma [17,46,47] frequencies and a decrease in delta frequencies [17,[44][45][46] during an entire night's NREM sleep [48]. It was also found that ID patients exhibited increased beta frequencies even during diurnal sleep, as observed in multiple sleep latency tests (MSLTs), and those with lower sleep efficiency and longer latency to MLST showed higher beta power also during night sleep [49].…”
Section: Discussionmentioning
confidence: 96%
“…For instance, “sleep state misperception,” also known as “paradoxical insomnia,” is a condition where individuals believe they are awake for most of the night, despite actually sleeping for a normal duration. This disorder is characterized by a significant discrepancy between perceived and actual sleep time, often associated with personality traits like neuroticism and altered brain activity during sleep, though its causes and prevalence remain under investigation [ 27 - 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Like behavioural responsiveness, subjective sleep perception does not align well with sleep stages [62][63][64][65]. Participants often overestimate their sleep onset latency: 26-50% of them still feel awake after the appearance of the first sleep spindle (N2 ; [1,62,66]). This overestimation of sleep latency could be linked to the asynchronous cortical deactivation found during the SOP, with some cortical areas that are still 'awake' (see previous Section).…”
Section: Internal Processing During the Sleep Onset Periodmentioning
confidence: 99%

Embracing sleep onset complexity

Lacaux,
Strauss,
Bekinschtein
et al. 2023
Preprint